DEMEND FOR THE PROFESSIONAL COUNSELOR'S WORK ACCORDING TO OPTIONS OF JUNIOR HIGH SCHOOL STUDENT'S PARENTS - PIETRUK, Witold (Trends in education, 2013)
The article shows the results of the survey conducted among the parents of the third class students attend to junior high schools in Brzeg district (Opole province). The aim of the research was the diagnosis if the professional counselor is needed in junior high schools according to parents' opinion. There is also shown a role of him in the vocational orientation system, as well as the scale of parents interest of his job and his attitude to planning the youth's educational and vocational path. The article also presents that parents are interested in help of professional counselor such as finding an appropriate school, job, choosing educational direction, showing the student his predisposition to a right vocational groups and presenting their advantages and disadvantages.
Keywords: A student of junior high school; parents; a school professional counselor